2024
DOI: 10.15282/construction.v4i1.10448
|View full text |Cite
|
Sign up to set email alerts
|

Shear Strength of Soft Soil Reinforced with Singular Bottom Ash Column

Muhammad Syamsul Imran Zaini,
Muzamir Hasan

Abstract: Structures construct on soft clays are often affected by stability and settlement problems due to high compressibility, low shear strength and low permeability of soft clay which will lead to bearing capacity failure and excessive settlement. The soft clay samples had the dimensions of 50 mm diameter and 100 mm in height. The bottom ash column had two (2) different area replacement ratios which were 4% and 9% (10 mm and 15 mm diameters respectively) with the bottom ash column penetration ratio of 0.3, 0.7 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Therefore, it can be concluded that utilizing CSA in SFSS can reduce the total cost of soil stabilization up to 10.06% (with 3% CSA utilization), 22.51% (with 6% CSA utilization), and 31.99% (with 9% of CSA utilization), while utilizing lime in SFSS can increase the total cost of stabilization up to 5.37% (with 3% lime utilization), 4.20% (with 6% lime utilization), and 3.30% (with 9% of lime utilization) compared to the utilization of cement as soil stabilizing agent. Nevertheless, due to the cost-effectiveness of CSA utilization in SFSS, this material is an ideal choice for stabilizing problematic and expansive soil [70][71][72] .…”
Section: Cost Analysismentioning
confidence: 99%
“…Therefore, it can be concluded that utilizing CSA in SFSS can reduce the total cost of soil stabilization up to 10.06% (with 3% CSA utilization), 22.51% (with 6% CSA utilization), and 31.99% (with 9% of CSA utilization), while utilizing lime in SFSS can increase the total cost of stabilization up to 5.37% (with 3% lime utilization), 4.20% (with 6% lime utilization), and 3.30% (with 9% of lime utilization) compared to the utilization of cement as soil stabilizing agent. Nevertheless, due to the cost-effectiveness of CSA utilization in SFSS, this material is an ideal choice for stabilizing problematic and expansive soil [70][71][72] .…”
Section: Cost Analysismentioning
confidence: 99%